Preparation, Characterization and Application of Polyaniline/silk Fibroin Composite. Issue 8 (October 2016) - Ahmad, Sharique; Sultan, Adil; Raza, Waseem; Muneer, M.; Mohammad, Faiz
We report the electrical properties and photocatalytic activity of polyaniline (Pani) and polyaniline/silk fibroin (Pani/SF) composite. The Pani/SF composite has been synthesized first time by chemical oxidative in-situ polymerization method by using potassium persulphate (K2 S2 O8 ) in an acidic medium. Thus prepared Pani and Pani/SF composite were characterized by using Fourier-transform infrared spectroscopy, x-ray diffraction, thermogravimetric analysis and scanning electron microscopy. The stability in terms of the DC electrical conductivity of Pani/SF composite and Pani was investigated under isothermal and cyclic aging conditions. Results indicated that the electrical properties of the composite were significantly influenced by the loading of SF to Pani and observed to be more thermally stable than those of Pani. As-prepared Pani and Pani/SF composites were studied for the degradation of methylene blue (MB) and Rhodamine B (RhB) under UV-light irradiations. The results showed that 91.4% & 85.4% degradation of RhB and MB takes place respectively after 90 min over Pani/SF composite. The decomposition rate of composite was 1.8-2.2 times greater than that of Pani. The improvement of photocatalytic activity of composite may be attributed to the electron-sink function of silk fibroin which increases the optical absorption property and separation of photogenerated charge carriers than Pani alone.